Produção de mudas de Cichorium endivia L. sob diferentes ambientes de crescimento - Almeida, Karlene Fernandes de (2023)
Chicory (Cichorium endivia L.) is part of the Asteraceae botanical family, presenting great economic importance within the oleraceous species cultivated in Brazil. One of the pillars in the horticultural sector is the production of high-quality and sustainable seedlings, through the rational use of resources. The production of vegetable seedlings under protected cultivation has expanded in recent years as it presents advantages over the traditional system. Among the various protected cultivation structures, one that has expanded is the use of colored or photoselective shading screens. In this sense, this work aimed to evaluate the development of seedlings of two chicory cultivars under black, silver and red shading screens, and in a greenhouse in the autumn and winter seasons of Marechal Cândido Rondon - PR. The experiment was conducted during the autumn and winter seasons of 2022, in the months of May and June (autumn) and July to August (winter), at the UNIOESTE Protected Cultivation Station. To conduct the experiment, the chicory cultivars Helena and Amazonas gigante were used. The design used was randomized blocks, with three replications and split plots. Assessments were carried out over a five-day interval, at 5, 10, 15, 20, 25, and 30 days after emergence (DAE) for both trials. The following were evaluated: plant height (cm); leaf area (LA) (cm2); Shoot dry matter mass (SDMM) (g); Root dry matter mass (RDMM) (g) and; growth analysis over the evaluation days. The use of shading screens and greenhouses, associated with the climatic conditions of the autumn and winter seasons, would interfere with the morphometry and growth of chicory seedlings. In autumn, for both the Helena cultivar and the Amazonas Gigante cultivar, the best agronomic performances were obtained for those plants grown in the greenhouse environment, with emphasis on the Amazonas Gigante cultivar. In winter, the environments provided different effects on the cultivars. Plants of the Helena cultivar performed better in the red screen environment. For the Amazonas Giant cultivar, the best performance was observed in those plants grown in the greenhouse.